2005
DOI: 10.1111/j.0959-9673.2005.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells in viral pathogenesis: protective or defective?

Abstract: SummaryDendritic cells (DC) are potent antigen-presenting cells that are critical in the initiation of immune responses to control and/or eliminate viral infections. Recent studies have investigated the effects of virus infection on the biology of DC. This review summarizes these changes, focusing on both the DC parameters affected and the viral factors involved. In addition, the central role of DC biology in the pathogenesis of several viral families, including herpesviruses, paramyxoviruses and retroviruses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 223 publications
(514 reference statements)
0
55
0
Order By: Relevance
“…1 However, a number of viruses are able to infect DCs, and several recent studies have investigated the effect of such infections on the biology of DCs. Although only very few studies report enhanced or unchanged functions of DCs after viral infection, most viruses seem to impair functional properties of DCs (for review, see Pollara et al 2 ). These data imply that viruses infect DCs as a strategy of immune escape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, a number of viruses are able to infect DCs, and several recent studies have investigated the effect of such infections on the biology of DCs. Although only very few studies report enhanced or unchanged functions of DCs after viral infection, most viruses seem to impair functional properties of DCs (for review, see Pollara et al 2 ). These data imply that viruses infect DCs as a strategy of immune escape.…”
Section: Introductionmentioning
confidence: 99%
“…2 In fact, there is 1 report that directly shows that measles virus infection of DCs can result in unstable DC-T-cell contacts and, as a consequence, in impaired T-cell activation. 3 Retroviruses, such as HIV, are also known to infect DCs and interfere with their maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies of virus-DC interactions focused predominantly on the outcomes of antiviral immune responses and the control of infection (36). More recently, however, it has been demonstrated that DCs play multiple roles in the pathogenesis induced by a variety of viruses, including human immunodeficiency virus (HIV), cytomegalovirus, measles virus, herpesvirus, influenza virus, and respiratory syncytial virus (3,28). In particular, DC participation in the immune response to the murine retrovirus mouse mammary tumor virus (MMTV) has been demonstrated.…”
mentioning
confidence: 99%
“…Second, Complex Diffusion is suitable for reducing the noise and enhancing the spots' edge, which would be advantageous in integrating with the ITE process as a whole. Pollara et al (2005). To test the methods proposed, the images in the data set are divided into many regions-of-interest and then processed using the selected methods with the whole range of α and β values, see equation (2).…”
Section: Resultsmentioning
confidence: 99%